2016
DOI: 10.1007/s12170-016-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Cardiovascular Risk Research: Impact of Pets on Cardiovascular Risk Prevention

Abstract: Animals interact with humans in multiple ways, including as therapy and service animals, commercially as livestock, as wildlife, and in zoos. But the most common interaction is as companion animals in our homes, with an estimated 180 million cats and dogs living in US households. While pet ownership has been reported to have many health benefits, the findings are inconsistent. Cardiovascular risk factors such as lipids, glucose, obesity, and heart rate variability have improved, worsened, or remained the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Some studies point to a preventative role of pet ownership in the development of CVD (see Schreiner, 2016). For example, systolic blood pressure was found to be significantly lower in a sample of pet owners than non-owners attending an Australian screening clinic for heart disease, even when controlling for body mass index and other health-related variables, for example, propensity to smoke (Anderson, Reid, & Jennings, 1992).…”
Section: Pets and Cardiovascular Healthmentioning
confidence: 99%
“…Some studies point to a preventative role of pet ownership in the development of CVD (see Schreiner, 2016). For example, systolic blood pressure was found to be significantly lower in a sample of pet owners than non-owners attending an Australian screening clinic for heart disease, even when controlling for body mass index and other health-related variables, for example, propensity to smoke (Anderson, Reid, & Jennings, 1992).…”
Section: Pets and Cardiovascular Healthmentioning
confidence: 99%
“…Studies have revealed that the presence of an animal can reduce the activity of the sympathetic nervous system, thus diminishing the risk of physical and mental stress [7]. Tsai et al [8] observed that heart rate and blood pressure decreased in the presence of a dog [9,10], as well as the opportunity for decrease in the cortisol blood level [11]. Presence of a dog during therapy could also leads to a reduction in the physical and mental pain subjectively perceived by the patient at a given moment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dog ownership or walking a dog seems to associate with additional physical activity or higher levels of physical activity in children as well as in adults [6][7][8][9]. Further, pet ownership may have a beneficial influence on psychological stress and symptoms of depression [10][11][12]. Both a physically active lifestyle and emotional well-being are known to associate with a reduced risk for T2D [13,14].…”
Section: Introductionmentioning
confidence: 99%